Analisis Perbandingan Dalam Kaedah Penentuan Zon Waktu Solat Di Malaysia: Comparative Analysis in Determining Method of Prayer Times in Malaysia - Nizam, Nurul Kausar; Mohd Nawawi, Mohd Saiful Anwar; Man, Sa'adan (Online Journal of Research in Islamic Studies, 2020)
Malaysia establishing the Time Zone Concept considering all zones as the determination of times for five daily obligatory prayers. Prayer times in Malaysia calculated by the Westernmost Point method which is based on a reference station located at the most Westernmost Point of the zone. Realizing the Westernmost Point is inconsistencies, Perak, Kedah and Penang had applied the Multiple Reference Point method. This method aims to resolve several issues such as the width zones in other use the single point as a reference. However, there are approach by using the isotime method and point based method in other to reform and improve the prayer times. Therefore, the study aimed to identify similarities and differences in implementation of these four methods. The study will be conducted using a qualitative approach in using a library research method and interviews. Through qualitative study, the findings of this paper indicate that the zoning system used depends on the appropriateness and suitability of the respective states. However, these four methods didn’t resolve issues of the width zones.